Novel conductive polypyrrole/zinc oxide/chitosan bionanocomposite: synthesis, characterization, antioxidant, and antibacterial activities - Ebrahimiasl, Saeideh; Zakaria, Azmi; Kassim, Anuar; Basri, Sri Norleha (Dove Medical Press, 2014)
An antibacterial and conductive bionanocomposite (BNC) film consisting of polypyrrole (Ppy), zinc oxide (ZnO) nanoparticles (NPs), and chitosan (CS) was electrochemically synthesized on indium tin oxide (ITO) glass substrate by electrooxidation of 0.1 M pyrrole in aqueous solution containing appropriate amounts of ZnO NPs uniformly dispersed in CS. This method enables the room temperature electrosynthesis of BNC film consisting of ZnO NPs incorporated within the growing Ppy/CS composite. The morphology of Ppy/ZnO/CS BNC was characterized by scanning electron microscopy. ITO–Ppy/CS and ITO–Ppy/ZnO/CS bioelectrodes were characterized using the Fourier transform infrared technique, X-ray diffraction, and thermogravimetric analysis. The electrical conductivity of nanocomposites was investigated by a four-probe method. The prepared nanocomposites were analyzed for antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl assay. The results demonstrated that the antioxidant activity of nanocomposites increased remarkably by addition of ZnO NPs. The electrical conductivity of films showed a sudden decrease for lower weight ratios of ZnO NPs (5 wt%), while it was increased gradually for higher ratios (10, 15, and 20 wt%). The nanocomposites were analyzed for antibacterial activity against Gram-positive and Gram-negative bacteria. The results indicated that the synthesized BNC is effective against all of the studied bacteria, and its effectiveness is higher for Pseudomonas aeruginosa. The thermal stability and physical properties of BNC films were increased by an increase in the weight ratio of ZnO NPs, promising novel applications for the electrically conductive polysaccharide-based nanocomposites, particularly those that may exploit the antimicrobial nature of Ppy/ZnO/CS BNCs.